6-Gingerol-rich fraction prevents disruption of histomorphometry and marker enzymes of testicular function in carbendazim-treated rats (2017)
Previous investigations demonstrated that 6-gingerol-rich fraction (6-GRF) prevented testicular toxicity via inhibition of oxidative stress and endocrine disruption in CBZ-treated rats. The influence of 6-GRF on alterations in histomorphometry and marker enzymes of testicular function in CBZ-treated rats which hitherto has not been reported was investigated in this study. The animals were orally administered either CBZ (50 mg/kg) alone or in combination with 6-GRF (50, 100 and 200 mg/kg) for 14 consecutive days. Histomorphormetric analysis demonstrated that 6-GRF significantly prevented CBZ-mediated increase in the organo-somatic index of the testes and seminiferous tubular diameter as well as the reduction in epithelium height and tubular length of testes in the rats. Similarly, 6-GRF ameliorated CBZ-induced disruption in the epithelium height as well as in the proportion of tubule and interstitium of the epididymis the treated rats. Furthermore, 6-GRF prevented CBZ-mediated increase in testicular acid phosphatase activity and the decrease in testicular alkaline phosphatase, aminotransferases, glucose-6- phosphate dehydrogenase and lactate dehydrogenase activities. Moreover, 6-GRF ameliorated CBZ-induced reduction in the testicular and epididymal sperm count and sperm motility in the treated rats. Conclusively, 6-GRF enhances key functional enzymes involve in spermatogenesis and maintains histo-architecture of testes and epididymis in CBZ-treated rats.